Assessing the function of the fronto‐parietal attention network: Insights from resting‐state fMRI and the attentional network test. Issue 4 (14th May 2013) - Markett, Sebastian; Reuter, Martin; Montag, Christian; Voigt, Gesine; Lachmann, Bernd; Rudorf, Sarah; Elger, Christian E.; Weber, Bernd
<x xml:space="preserve">Abstract</x> In the recent past, various intrinsic connectivity networks (ICN) have been identified in the resting brain. It has been hypothesized that the fronto‐parietal ICN is involved in attentional processes. Evidence for this claim stems from task‐related activation studies that show a joint activation of the implicated brain regions during tasks that require sustained attention. In this study, we used functional magnetic resonance imaging (fMRI) to demonstrate that functional connectivity within the fronto‐parietal network at rest directly relates to attention. We applied graph theory to functional connectivity data from multiple regions of interest and tested for associations with behavioral measures of attention as provided by the attentional network test (ANT), which we acquired in a separate session outside the MRI environment. We found robust statistical associations with centrality measures of global and local connectivity of nodes within the network with the alerting and executive control subfunctions of attention. The results provide further evidence for the functional significance of ICN and the hypothesized role of the fronto‐parietal attention network. Hum Brain Mapp 35:1700–1709, 2014. © 2013 Wiley Periodicals, Inc.